El ciudadano José Chávez y Castillo vocal secular ... de la Excmo. Asamblea Departamental del N. México . - Chávez y Castillo, José ([publisher not identified], 1845)
Announcement of the Mexican Congress' confirmation of Gen. José Joaquín de Herrera as President of the Republic.